Students’ Perceptions on the Digital Literacy and Writing Skills Using Local Indigenous Poem: Google Gemini Interactive Multimedia Approach - Arwan Arwan; Sri Suryaningsih; Ikra Ikra; Rahmatia Ardila; Mulyati Mulyati; Indra Indra (International Journal of Language Education, 2026)
This study aims to explore students’ perceptions of digital literacy and writing skills using an interactive multimedia platform based on Kapatu Mbojo local literature, integrated with Google Gemini. Grounded in multimedia learning theory, which emphasizes integrating text, visuals, and audio to enhance instructional effectiveness, this research involved 143 high school students and 6 Indonesian language teachers from two schools in Bima Regency, Indonesia. The findings reveal that most students responded positively across five key aspects: digital literacy, ease of using Google Gemini, improvement in writing skills, interest in local culture, and an overall enjoyable learning experience. The use of this media significantly improved students’ writing scores, as evidenced by notable gains from pre-test to post-test. Additionally, students reported increased motivation and autonomy in writing, which was supported by real-time feedback from Google Gemini. The study suggests that integrating artificial intelligence and local culture into instructional media can simultaneously enhance digital literacy and writing competence. It is recommended that similar interactive multimedia tools be developed and implemented across various educational contexts, alongside teacher training programs to maximize the pedagogical benefits of AI-driven, contextually relevant learning.